ASSESSMENT OF Candida SPP. PROLIFERATION IN OCCLUSAL AND PALATAL SPLINTS - Rode, Sigmar de Mello [UNESP]; Joias, Renata Pilli; Oliveira, Jonatas Rafael de [UNESP]; Mattos, Maria Fernanda [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Silva, Michelle Perreluppi [UNESP]; Libonati Seixas, Ellen Cristina (Univ Federal Uberlandia, 2018)
Candida species inhabit the oral cavity of all individuals who wear complete denture and whose material is the same as that used in splints. Assess the growth of C. albicans in occlusal and palatal splints used for treatment of TMD so that the potential risks of oral microbiota can be assessed. The growth of Candida spp. was assessed in the saliva of 27 individuals wearing splints for treatment of TMD. They were divided into two groups: G1 (n = 14), individuals wearing occlusal splint; and G2 (n = 13), individuals wearing palatal splint. Saliva samples were collected during placement of the splints (T1) and after 4 months (T2), being stored in PBS (10 mL) after 60-second rinses. It was observed that patients wearing occlusal splints (G1) had an increase of 0.648 CFU/mL (Log 10), with statistically significant differences (P = 0.043) for C. albicans (42.33%), C. glabrata (5.52%), C. krusei (41.72%) and C. tropicalis (10.43%). In the group of patients wearing palatal splints (G2), there was a decrease of 0.101 CFU/mL (Log 10), was observed with (P = 0.964) only the presence of C. albicans. The results suggest that growth of Candida species was greater in patients wearing occlusal splints compared to those wearing palatal ones as the presence of different yeast species was found in the former.
Keywords: Candida; Colony-forming units; Muscle relaxant splints